2011
DOI: 10.1002/adsc.201100415
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Coupling of Alkynes with Acrylates by Recyclable Oxide‐Supported Ruthenium Catalysts: Formation of Distorted Ruthenium(IV)‐oxo Species on Ceria as a Key Precursor of Active Species

Abstract: A solid ceria-supported ruthenium catalyst (Ru/CeO 2 ) as well as a zirconia-supported ruthenium catalyst (Ru/ZrO 2 ) showed high activities toward the intermolecular coupling of alkynes with acrylates to give the corresponding 1,3-dienes in high yields. The reaction proceeded in the presence of sodium formate and both internal or terminal alkynes and norbornene could be applied for the catalytic systems. The solid ruthenium catalyst could be recycled for several times without significant loss of activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 68 publications
3
10
1
Order By: Relevance
“…On the other hand, the spectra of SiO 2 , Al 2 O 3 , and TiO 2 ‐supported catalysts were very close to that of rutile‐type RuO 2 . The Fourier transforms of the Ru K‐edge extended X‐ray absorption fine structure (EXAFS) spectrum of Ru/CeO 2 also suggested the presence of highly dispersed Ru species on CeO 2 11e,f. In the present study, we deduce that such a surface ruthenium(IV)–oxo species is a key precursor to the catalytically‐active species for linear dimerization.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…On the other hand, the spectra of SiO 2 , Al 2 O 3 , and TiO 2 ‐supported catalysts were very close to that of rutile‐type RuO 2 . The Fourier transforms of the Ru K‐edge extended X‐ray absorption fine structure (EXAFS) spectrum of Ru/CeO 2 also suggested the presence of highly dispersed Ru species on CeO 2 11e,f. In the present study, we deduce that such a surface ruthenium(IV)–oxo species is a key precursor to the catalytically‐active species for linear dimerization.…”
Section: Resultssupporting
confidence: 56%
“…No RuO 2 crystallites could be observed in the XRD pattern of Ru/CeO 2 , which indicates the high dispersion of Ru species on ceria. Note that we previously revealed the formation of a distorted ruthenium(IV)–oxo species exclusively on CeO 2 and ZrO 2 through a spectroscopic study and that RuO 2 ‐like species are formed on other supports:11e,f in the Ru K‐edge X‐ray absorption near‐edge structure (XANES) spectrum of Ru/CeO 2 , a pre‐edge peak appeared at 22 110 eV, which is characteristic of ruthenium(IV)–oxo species in a distorted coordination environment (see Figure 2). On the other hand, the spectra of SiO 2 , Al 2 O 3 , and TiO 2 ‐supported catalysts were very close to that of rutile‐type RuO 2 .…”
Section: Resultsmentioning
confidence: 95%
“…The XANES spectrum of unmodified Ru/CeO 2 showed a characteristic pre-edge peak at around 22110 eV, which can be assigned to Ru(IV) species with a distorted coordination structure bearing a RuO bond. 46,50 After dppb-treatment, the pre-edge peak disappeared, and the absorption-edge of the catalyst shifted to a lower energy but did not coincide with that of Ru metal. This result indicates that the Ru(IV) species are reduced to lowvalent Ru species, probably Ru(II) species, with a loss of the RuO structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…42−47 Our latest spectroscopic investigations showed that Ru(IV)O species on CeO 2 were transformed into low-valent Ru species with high catalytic activities. 46,47 In the course of these studies, we found that the heating of Ru/CeO 2 catalysts in a hydrogen atmosphere in the presence of a small amount of phosphines (phosphine modification route) greatly improved the activities of the resulting Ru catalysts for the arylation 44 and alkylation 45 of aromatic C−H bonds. Furthermore, unmodified Ru/CeO 2 catalysts were found to be effective for the addition of carboxylic acids to terminal alkynes to give the (E)-isomer of vinyl esters as major products.…”
Section: ■ Introductionmentioning
confidence: 98%
“…The success of our first attempt prompted us to examine the effectiveness of Ru/CeO2 as a solid catalyst alternative to low-valent ruthenium complex catalysts, and we have revealed that Ru/CeO2 could realize various organic transformations, including reactions that proceed C _ H bond activation 40) 46) . Some of these reactions are effectively promoted by the Ru/CeO2 catalyst together with a small amount of additives 41), 42) , and some other reactions require the reductive treatment of Ru/CeO2 in the presence of specific phosphines 43),44), 46) . The present account describes our recent results in the development of a Ru/CeO2-based catalytic system for use in environmentally-benign organic transformations.…”
Section: Introductionmentioning
confidence: 99%